2007
DOI: 10.1017/s113874160000651x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Starvation in the Rat: Running versus Eating

Abstract: Rats given the combination of unrestricted access to an activity wheel and restricted access to food can lose weight to the extent that they will die unless removed from these conditions. Although this has been known for forty years, why this happens has remained unclear. The phenomenon is paradoxical in that one might expect such rats to eat more as their weight decreases, but in fact they eat less than resting controls. This lecture first examines some of the factors than influence whether self-starvation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
2
14
0
4
Order By: Relevance
“…Finally, the low EE described in both FR and FRW mice, especially during the light period when only FRW showed FAA, led us to conclude that EE not only was related to exercise but reflected an adaptive way to save energy to maintain physiological functions. The impact of food restriction on energy metabolism confirmed data obtained with 30% of food restriction (8). However, the strategy used by FR and FRW mice were different.…”
Section: E250supporting
confidence: 76%
See 1 more Smart Citation
“…Finally, the low EE described in both FR and FRW mice, especially during the light period when only FRW showed FAA, led us to conclude that EE not only was related to exercise but reflected an adaptive way to save energy to maintain physiological functions. The impact of food restriction on energy metabolism confirmed data obtained with 30% of food restriction (8). However, the strategy used by FR and FRW mice were different.…”
Section: E250supporting
confidence: 76%
“…Regarding self-starvation as part of a cognitive/emotional aspect of the disease proved difficult, even impossible, to mimic in mice. Indeed, in the ABA model, the self-starvation, which is not always observed (36), might be related to physiological adaptations to maintain thermogenesis and to compensate for the dryness of the pellets since the presentation of humidified pellets during the 2-h time-restricted feeding or an increasing of the room temperature led to the disappearance of the voluntary food restriction (7,8). These data support more adaptations to physiological changes than a cognitive drive to reduce feeding.…”
mentioning
confidence: 81%
“…Food restriction in animals, for example, leads to an increase, not a decrease, in energy expenditure (Boakes, 2007;Routtenberg and Kusnezov, 1967), and increased rather than decreased risktaking in terms of coming out of cover in the presence of predators (Krause et al, 1998). Food-restricted animals of many different species also switch from preferring less variable to more variable food sources (Caraco et al, 1980;Kacelnik and Bateson, 1996), in line with the predictions of risk-sensitive foraging theory (Stephens, 1981).…”
Section: Introductionsupporting
confidence: 53%
“…However, as specified by Klenotich and Dulawa (2012), the ABA paradigm is strongly dependent upon factors that amplify or reduce some parts of the phenotype, i.e., the choice of rodent strain (more or less resistant to ABA, Gelegen et al, 2007), the sex of animal (female are more vulnerable to ABA), the age (younger animals are more susceptible to ABA), the temperature (increasing the temperature to 32°C strongly reduces the ABA behavior, Cerrato et al, 2012), the time of the day the animals receive food, and the hydration/dryness of the food. In fact, Boakes and Juraskova, 2001; Boakes, 2007) demonstrated that the “self-starvation” observed in ABA rats might reflect both the reduced palatability of the dry chow for a dehydrated animal and satiety signals from a stomach full of water. Thus, giving hydrated food during the 1 h-feeding schedule completely abolishes the ABA phenotype (rapid weight loss, hyperactivity, etc.).…”
Section: Physiological Alterations In Anorexia Nervosamentioning
confidence: 99%